Optimization of the amount of gas moles determination through Boyle’s law and Gay-Lussac’s law experiments - Kunlestiowati Hadiningrum; Ratu Fenny Muldani (Journal of Physics: Theories and Applications, 2018)
Boyle’s Law describes the inverse relationship between absolute pressure and air volume, if the temperature is constant in a closed system. Gay Lussac’s Law states that the pressure of a gas mass is directly proportional to the absolute temperature of the gas, when the volume is held constant. The macroscopic quantity associated with both laws includes the number of moles of gas. The purpose of the study is to calculate the number of moles of gas through Boyle’s Law and Gay Lussac’s Law experiments. The experimental results were confirmed by calculating the number of moles theoretically, so that it can be concluded that the experimental device settings which the closest to the theoretical results. The Boyle’s Law experimental results with a pipe cross-sectional area of 54.08 mm2, at a temperature of 295 K obtained 4.67 x 10-4 moles, its relative uncertainty is 7.60%, at a temperature of 299.1 K obtained 3.97 x 10- 4 moles, the relative uncertainty value is 0.51%, and at a temperature of 299.5 K obtained 5.20 x 10-4 moles, the relative uncertainty value is 12.56%. The average relative uncertainty value of the three experiments is 6.89%. The results of the Gay Lussac’s Law experiment, at a gas volume of 0.578 x 10-3 m3, obtained the number of moles in a row of 1.38 x 10-2 moles, 1.83 x 10-2 moles and 1.33x 10-2 moles, theoretical calculation of 2.14 x 10-2 moles. The average value of the relative uncertainty of the three experiments is 24.3%. Based on these results, it can be concluded that the results of calculating the number of moles through Boyle’s Law experiments are closest to theoretical calculations.